Pengukur Cas Berdigit - Muda, Normala (Universiti Sains Malaysia, 2006)
Digital Charge Measurement Device is designed to measure value of charge on body and room and also to detect the polarity of charge. This design using an element of capacitor to produce the charge differences between two plates of capacitor. Beside that, capacitor also can charge or discharge. This design also using operational amplifier to amplify the charge differences. Others, analog to digital converter are used to convert analog signal to digital signal. Displays in digital value are easy to read and also more accurate than metre analog. As a conclusion, the motive of this design is to produce one product that can measure value of charge on body and room and also to detect the polarity that charge. So that customer can take prevention step or prepare early to prevent damage on variety of electronic components through discharging of charge on body while using those components.